The role of lysosomal peptidases in glioma immune escape: underlying mechanisms and therapeutic strategies - Liu, Hao; Peng, Jie; Huang, Linzhen; Ruan, Dong; Li, Yuguang; Yuan, Fan; Tu, Zewei; Huang, Kai; Zhu, Xingen (Frontiers in Immunology, 2023)
Abstract Glioblastoma is the most common primary malignant tumor of the central nervous system, which has the characteristics of strong invasion, frequent recurrence and rapid progression. These characteristics are inseparable from the evasion of glioma cells from immune killing. This makes immune escape a great obstacle to the treatment of glioma, and studies have confirmed that glioma patients with immune escape tend to have poor prognosis. In the immune escape process of glioma, the lysosomal peptidase family in lysosomes plays an important role. The lysosomal peptidase family mainly includes aspartic acid cathepsin, serine cathepsin, four families of asparagine endopeptidases and cysteine cathepsins. Among them, the cysteine cathepsin family plays a prominent role in the immune escape of glioma. Numerous studies confirmed that glioma immune escape mediated by lysosomal peptidases has something to do with autophagy mechanism, cell signaling pathway, immune cells, cytokines and other mechanisms, especially lysosome organization The relationship between protease and autophagy is more complicated, and the current research is not complete and in-depth. This article reviews how lysosomal peptidases mediate the immune escape of glioma through the above mechanisms. And explore the possibility of lysosomal peptidase as the target of glioma immunotherapy. Keywords: lysosomal peptidases, glioma, immune escape, autophagy, cell signal pathways, cathepsin